2003
DOI: 10.1074/jbc.m300402200
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Golgi Protein Transport Depends on a Cholesterol Balance in the Lipid Membrane

Abstract: Transport of proteins between intracellular membrane compartments is mediated by a protein machinery that regulates the budding and fusion processes of individual transport steps. Although the core proteins of both processes are defined at great detail, much less is known about the involvement of lipids. Here we report that changing the cellular balance of cholesterol resulted in changes of the morphology of the Golgi apparatus, accompanied by an inhibition of protein transport. By using a well characterized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 76 publications
5
41
1
Order By: Relevance
“…First, the TGN pool of the enzyme contracted in size by up to 50%, and second, there was a visible vesicularization of the eGFP-PI4KII ␣ -containing membranes. These observations are consistent with the previously described effects of M ␤ CD on TGN membranes ( 24,43,44 ) . In addition, M ␤ CD treatment had dramatic effects on cellular sterol levels as imaged by fi lipin staining ( Fig.…”
Section: ␤ CD Treatment Affects the Morphology Of Pi4kii ␣ -Rich Mesupporting
confidence: 82%
See 2 more Smart Citations
“…First, the TGN pool of the enzyme contracted in size by up to 50%, and second, there was a visible vesicularization of the eGFP-PI4KII ␣ -containing membranes. These observations are consistent with the previously described effects of M ␤ CD on TGN membranes ( 24,43,44 ) . In addition, M ␤ CD treatment had dramatic effects on cellular sterol levels as imaged by fi lipin staining ( Fig.…”
Section: ␤ CD Treatment Affects the Morphology Of Pi4kii ␣ -Rich Mesupporting
confidence: 82%
“…This differs from others who concluded that differences in protein mobility do not necessarily refl ect confi nement to lipid rafts ( 65 ). In the case of PI4KII ␣ , the differences in protein mobility that we observed can be rationalized by overall M ␤ CDinduced changes to membrane morphology and connectivity ( 24,43,44 ) without the need to invoke the targeting of PI4KII ␣ to lipid rafts. In particular, our photobleaching analysis demonstrated that M ␤ CD-induced changes to membrane structure limit the pool of fl uorophore available to replenish the photobleached spot, and this manifests as a reduced mobile fraction of eGFP-PI4KII ␣ .…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Unexpectedly, anterograde transport at the Golgi is exquisitely sensitive to changes in the cholesterol concentration [25,26], possibly because this leads to improper segregation of lipids and proteins [27] or to incorrect disposition of proteins on the cytosolic surface. In yeast, membrane flux through the exocytic pathway is regulated by cytosolic Sec14 [28], a family of cytosolic phosphatidylcholine/phosphatidylinositol transfer proteins that via their dual specificity may act as sensors of lipid composition and adapt lipid metabolism.…”
Section: Lipid-binding Proteins and Vesicle Fluxmentioning
confidence: 99%
“…A consequence of chronic missorting to late endosomes would be eventual depletion from the Golgi of recycling glycosphingolipids and probably concomitant depletion of associated cholesterol (Brown, 1998;Marks and Pagano, 2002;van Meer, 2002). Although glycosphingolipid deficiency per se does not result in Golgi dispersal (Sprong et al, 2001), depletion or enhancement of Golgi cholesterol is known to affect Golgi distribution and intra-Golgi transport (Stüven et al, 2003), as well as the requirement for the kinesin family member KIFC3 in Golgi motility (Xu et al, 2002). Cell-to-cell variation in cholesterol or glycosphingolipid content might explain why only 50-65% of tGolgin-1-depleted cells show Golgi dispersal, and cholesterol depletion might explain the reduced steady-state localization of a glycosylphosphatidylinositol-linked protein to the plasma membrane in cells overproducing a tGolgin-1-derived peptide (Kakinuma et al, 2004).…”
mentioning
confidence: 99%